Synthesis and characterization of di-nuclear bis(benzotriazole iminophenolate) cobalt complexes: catalysis for the copolymerization of carbon dioxide with epoxides12. Issue 32 (24th July 2019) - Su, Yu-Chia; Tsai, Chen-Yen; Huang, Li-Shin; Lin, Chia-Her; Ko, Bao-Tsan
Abstract : New structurally well-defined di-nuclear Co(ii )/Co(ii ) or Co(ii )/Co(iii ) complexes containing a BiIBTP ligand and carboxylate coligands were synthesized for CO2 /epoxide copolymerization. Abstract : A family of di-nuclear bis(benzotriazole iminophenolate) (BiIBTP) cobalt complexes containing diverse ancillary carboxylate derivatives have been synthesized and structurally characterized. The one-pot synthesis of the BiIBTP ligand precursor with cobalt perchlorate salt (2.0 equiv.) and carboxylic acid derivatives (2.0 or 5.0 equiv.) in the presence of triethylamine (5.0 equiv.) under refluxing methanolic solution generated bimetallic di-carboxylate Co(ii )/Co(ii ) complexes [( C83C BiIBTP)Co2 (O2 CR)2 ] (R = C6 H5 (1 ), C6 F5 (2 ), 4-CF3 –C6 H4 (3 ), 4-OMe–C6 H4 (4 ), CF3 (5 )) in ≧65% yields. Interestingly, the Co(ii )/Co(iii ) mixed-valence complex6 resulted from the treatment of1 with silver perchlorate (1.0 equiv.) as the oxidizing agent under an O2 -atmosphere in 50% yield. The crystal structure of6 reveals an ionic and di-nuclear benzoate species composed of a cationic moiety formulated as [( C83C BiIBTP)Co2 (O2 CC6 H5 )2 ] + and a counterbalanced perchlorate anion, and both metal atoms are attributed to hexa-coordinated cobalt ions with varied coordination environments. Catalysis results of CO2 /epoxide copolymerization indicated that complex1 was more efficient than2–6 where compound6 was shown to be the least active. Co complex1 incorporating benzoate coligands was demonstrated to effectively catalyze the CO2 -copolymerization of cyclohexene oxide (CHO), 4-vinyl-1, 2-cyclohexene oxide or cyclopentene oxide, producing the associated CO2 -based polycarbonates with >99% carbonate repeated units under optimal conditions. Not only the controllable character of complex1 for CO2 /CHO copolymerization is enabled, but also1 has been shown to catalyze such a copolymerization in the "immortal" manner. Using the same di-cobalt catalyst in combination with excess ratios of neopentyl glycol (up to 150 equiv.) as the chain transfer agent could give low molecular weight poly(cyclohexene carbonate) polyols with monomodal molecular weight distributions. This work offers the facilely prepared di-nuclear cobalt complexes as catalysts for the efficient catalysis of CO2 -copolymerization.